The methodology and practice of econometrics : a festschrift in honour of David F. Hendry - Hendry, David F.; Castle, Jennifer; Shephard, Neil. (Oxford ; New York : Oxford University Press, 2009)
This volume is a collection of original research in time-series econometrics, both theoritical and applied. It is broadly divided into five sections, including model selection, correlations, forecasting, methodology and empirical applications.
Includes bibliographical references and index.
nmn 29/04/13
Loans
Keywords: Econometrics; Econometric models